1987
DOI: 10.1063/1.453665
|View full text |Cite
|
Sign up to set email alerts
|

Fluids in micropores. I. Structure of a simple classical fluid in a slit-pore

Abstract: Equilbrium properties of a rare-gas fluid contained between two parallel fcc(100) planes of rigidly fixed rare-gas atoms were computed by means of the grand-canonical ensemble Monte Carlo method. The singlet distribution function ρ(1), and the pair-correlation function g(2) in planes parallel to the solid layers, indicate that the structure of the pore fluid depends strongly on the distance h between the solid layers. As the separation increases from less than two atomic diameters, successive layers of fluid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
115
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(118 citation statements)
references
References 13 publications
3
115
0
Order By: Relevance
“…Theoretical work and computer simulations of Lennard-Jones fluids and hard spheres show that the oscillatory solvation force originates from the stratification or ordering of the molecules in layers when the fluid is confined by the surfaces [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical work and computer simulations of Lennard-Jones fluids and hard spheres show that the oscillatory solvation force originates from the stratification or ordering of the molecules in layers when the fluid is confined by the surfaces [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical work and computer simulations of Lennard-Jones fluids and hard spheres show that the oscillatory solvation force originates from the ordering of the molecules in layers when the fluid is confined by the surfaces. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] For finite ranged wall-fluid and fluid-fluid potentials, the solvation force shows an oscillatory behavior at high liquid densities and a pure exponential decay at low liquid densities, provided the liquid is sufficiently far from the critical point and no phase transition will occur.…”
Section: Introductionmentioning
confidence: 99%
“…Such solid sliding is a major cause of frictional dissipation, and can persist even in the presence of lubricants (1). At a nanotribological level, surface force balance (SFB) measurements, supported by theory and computer simulations, have shown that when simple organic liquids are confined between atomically smooth, solid (mica) surfaces to films thinner than some six to eight molecular layers, they may become solid-like, and are often layered (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Subsequent sliding of the surfaces across such films when they are subjected to shear may then take place via stick-slip motion (15,16).…”
mentioning
confidence: 99%